Juridical Analysis of Criminal Perpetrators of Electronic Gambling Transaction Information - Annie Myranika; Haji Awg Asbol Bin Haji Mail (The International Journal of Law Review and State Administration, 2024)
The aim and use of the research is to analyze the legal regulation of gambling crimes. To analyze the Tangerang District Court Decision No.794/Pid.Sus/2018/PN.Tgn. against perpetrators of ITE crimes. To analyze legal obstacles in dealing with perpetrators of ITE crimes. The research method uses normative law which places law as a system of norms, regarding principles, norms, rules of statutory regulations, and court decisions. Data collection techniques in research include primary, secondary, and tertiary legal materials. Data analysis is the process of analyzing and sorting data into patterns, categories, and basic units of description so that themes can be found and formulated. Conclusion: The legal regulations for gambling crimes in Indonesia are regulated in the provisions of Articles 303 and 303 bis of the Criminal Code, Law no. 7 of 1974 concerning the Control of Gambling. analysis of the evidentiary system in force in Indonesia is that the Tangerang District Court judge in decision no. 794/Pid.Sus/2018/ PN.Tgn. Obstacles to law enforcement for perpetrators of special gambling crimes committed online consist of internal factors such as lack of mastery and understanding of information technology, means and facilities for finding evidence, and servers created by online bookies which are often located in countries where it is legal. gambling, as well as the ease of downloading VPN applications by online gambling players